Ventral extra-striate cortical areas are required for optimal orientation averaging - Allen, Harriet A.; Humphreys, Glyn W.; Bridge, Holly (Elsevier, 2007)
We examined the ability of a previously well-studied patient with visual agnosia to compute the average orientation of elements in visual displays. In a structural MRI study, we show that the lesion is likely to involve a variety of ventral extra-striate areas, including V2, V3 and V4; however, the lesion does not extend dorsally. Subsequently we show that some ability to compute average orientation is spared, though there are limitations on the ability to scale the averaging process as a function of the numbers of elements. The results suggest that some aspects of orientation averaging can be accomplished in spared regions of V1 but flexible averaging requires ventral extra-striate cortex.